Corporate Internal Investigations 4.0 - Túlio Felippe Xavier Januário (Revista Brasileira de Direito Processual Penal)
The aim of the present paper is to analyze the criminal procedural implications of applying artificial intelligence systems in the context of internal investigations. More specifically, we will seek to answer the following questions: how can AI be used in these procedures and which are its legal boundaries? In case of effective use of this technology, how can it, in a future criminal proceeding, affect the admissibility and valuation of elements of information derived from internal investigations? In order to address these questions, we will apply the deductive methodology with a review of European and Brazilian legislation, doctrine and jurisprudence. At the end of the paper, we will demonstrate the limits to be observed for the processing of data and the use of AI in the scope of internal investigations, as well as the requirements and limits of sharing the information obtained from them with criminal proceedings.